A beginner's guide to Dante's Divine comedy - Baxter, Jason M., 1981- (Grand Rapids, Michigan : Baker Academic, a divison of Baker Publishing Group, 2018)
Dante's Divine Comedy is widely considered to be one of the most significant works of literature ever written. It is renowned not only for its ability to make truths known but also for its power to make them loved. It captures centuries of thought on sin, love, community, moral living, God's work in history, and God's ineffable beauty. Like a Gothic cathedral, the beauty of this great poem can be appreciated at first glance, but only with a guide can its complexity and layers of meaning be fully comprehended. This accessible introduction to Dante, which also serves as a primer to the Divine Comedy, helps readers better appreciate and understand Dante's spiritual masterpiece. Jason Baxter, an expert on Dante, covers all the basic themes of the Divine Comedy, such as sin, redemption, virtue, and vice. The book contains a general introduction to Dante and a specific introduction to each canticle (Inferno, Purgatorio, and Paradiso), making it especially well suited for classroom and homeschool use. -- ‡c From publisher's description.
Introduction: Dante as Poet, Prophet, and Exile -- Part 1: INFERNO -- Zooming In and Zooming Out: How to Read Inferno (Inferno 1-2) -- The Fear of Hell and the Fear of God (Inferno 3-9) -- The Graveyard of the Heretics and the Wasteland of the Violent (Inferno 10-17) -- White-Collar Criminals and Sins against Words (Inferno 18-26) -- Icy Hearts and Frozen Souls: The Lowest Portion of Hell (Inferno 27-34) -- Part 2: PURGATORIO -- Waiting for God: An Introduction to Purgatorio -- The People outside the Gate: Freedom, Responsibility, and Vulnerability (Purgatorio 1-9) -- In Search of Deep Cleansing: The Middle Canti (Purgatorio 10-24) -- Returning to Humanity's First Home: Epic and Lyric in the Garden of Eden (Purgatorio 25-28) -- "As the Heavens Are Higher Than the Earth": Dante's Apocalyptic Vision (Purgatorio 29-33) -- Part 3: PARADISO -- "Great Fires Come from Tiny Sparks": An Introduction to Paradiso (Paradiso 1-2) -- "In His Will Is Our Peace": Individuality and Polyphony in Paradiso (Paradiso 3-20) -- Intellectual Fasting and the Test of Love: Saturn, Stars, and the Crystalline Sphere (Paradiso 21-29) -- The Canti of Surprise: Garden, Book, and Rose (Paradiso 30-33) -- Conclusion: The Wonder of the Comedy.
Includes bibliographical references and index.
Keywords: Dante Alighieri, -- 1265-1321.; Dante Alighieri, -- 1265-1321 -- Criticism and interpretation; Dante Alighieri, -- 1265-1321.; Divina commedia (Dante Alighieri); Christianity in literature; Religion and literature; Criticism, interpretation, etc